Il miglior caffè di Venezia: Quali collaborazioni architettoniche per il "nuovo regime climatico"? - Yaneva, Albena (Studi e ricerche di storia dell'architettura, 2025)
The 19th edition of the Venice Biennale of Architecture encouraged collaborations between disciplines that are commonly perceived as unlikely companions. A key task of the curatorial team was to facilitate connections among a range of scientists and designers — from fields as varied as physics, forestry, microbiology, data science, AI, nanoscience, network science, anthropology, and naval engineering — so they could embark on a shared creative process. In this article I discuss one noteworthy installation that exemplifies this approach: the Canal Café project by Diller Scofidio + Renfro (DS+R) studio, a collaboration between architects, water engineers, and purification experts. To trace the partnerships that proved so essential for the project’s realisation, I shadowed the curatorial team, interviewed architects from DS+R and followed the installation’s development from December 2024 until the vernissage in May 2025. By examining their work together and the concentration of collaborative processes, I argue that this case compels us to rethink the scenography of work of designers in the “new climatic regime”.